Why Bother? A Socio-Theological Inquiry into Dimensions of Compassion in the Boomer Culture of Ottawa - Marsden-Dole, Patricia M. (Université Saint-Paul / Saint Paul University, 2014)
Ontario will soon become an aging society (2017) at a time when this once rich province has become a have not province in Canada according to definitions used to assess federal-provincial transfer payments. In the past half century since the 1960’s the public culture has shifted from one dominated by Anglo-Saxon Christian values and social norms to one that is highly urbanized and multicultural seeking to welcome and balance the values and norms of many cultures and faiths. Much has changed in the life time of what is now the aging Boomer generation. Practical theology provides an approach to practical moral reasoning and practical wisdom in the light of Christian tradition with which to engage in the ethical and moral challenges in contemporary culture. From the perspective of Christian tradition compassion at the collective and personal levels will be essential to ensure that future generations have the means with which to carry forward the tradition of a just and caring society. Such a society must demonstrate respect for human dignity of the individual while assuming a collective responsibility for the common good by engaging the voices of people most affected by the interests of the powerful. Compassion needs hope, and hope needs faith in something life giving. This dissertation presents an approach for young seniors with which to begin to create this future through locating in their life stories the sources of faith that inspires hope in life with the freedom to sustain compassionate engagement with those on the margins of society, particularly frail elders in the years ahead. ix
Keywords: culture; faith; compassion; baby boomers; meaning in life